ANALISIS VOLATILITAS ARUS KAS, TINGKAT HUTANG DAN SIKLUS OPERASI TERHADAP PERSISTENSI LABA (Studi Kasus pada PT. Timah (Persero) Tbk Pangkalpinang) - Monica Lee, Ria; Panjaitan, Fery; Hasibuan, Romulus (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
The aim of this study is to analyze the volatility of cash flow, debt level, and operating cycle to earnings persistence. The object of this research used by the researcher is a case study of PT. Timah (Persero) Tbk. The company is engaged in tin mining and has been listed on the Indonesia Stock Exchange since 1995. PT. Timah (Persero) Tbk is a producer and exporter of tin. The scope of activities of the Company includes the areas of mining, trade, transportation, and services. The data collected are historical data and descriptive quantitative methods are used to describe issues related to independent variable statements. The analysis is done by using multiple regression. The results showed that the volatility of cash flow, debt level, and operating cycle have a significant positive effect on earnings persistence. The volatility of cash flows has a positive effect of 212,451 with a significant level of 0.002 on earnings persistence, the level of debt has a positive effect of 27, 637 with a significant level of 0.001 on earnings persistence, the operating cycle has a positive effect of 9,056 with a significant level of 0,000 towards earnings persistence, and cash flow volatility, debt level, the operating cycle can influence and increase earnings persistence simultaneously. Based on the calculation of Fcount 256, 762 is greater than Ftable 216 with a significant level of 0, 000.